Effect of Proactive Marketing Management Capability on Marketing Survival of Instant and Convenience Foods Businesses in Thailand - Krokaew, Yuthachai; Jhundra-Indra, Prathanporn; Boonlua, Sutana (JOURNAL OF SOUTHERN TECHNOLOGY, 2017)
The main purpose of this research is to investigate the effect of proactive marketing management capability on marketing survival. Data were collected from 163 instant and convenience foods firms in Thailand by questionnaire mail survey. The ordinary least square regression is employed to analyze in this research. The results reveal that two dimensions of proactive marketing management capability including customer learning dynamism and market leading implementation have a significant positive association with marketing goal achievement and marketing survival, while product innovation intelligence only significant positive association with marketing survival. Furthermore, marketing goal achievement has a positive influence on marketing survival. This research helps to fulfill the understanding towards the proactive marketing management capability in the context of Thai instant and convenience foods firms.